MOOC Platforms: a Review and Comparison - Gusti Salamah, Ummy; Alayham Abbas Helmi, Rabab (International Journal of Engineering and Technology, 2018)
For development courses in the Massive Open Online Courses (MOOC) requires the support of good technological infrastructure. Some MOOC platforms are part of the institution but some platforms are built by individual teachers or instructors. The objective of this study to reviews about characteristics in MOOC platforms and evaluation of comparison based on previous studies with specific in MOOC platforms. The databases in MOOC studies found in four databases namely Google Scholar, IEEExplore, Elsevier Science Direct, and Emerald. After the databases filtered, 20 papers in MOOC studies that selected and 4 databases related in development Open Learning and Udemy platforms. This study aims to bring the knowledge for the developer or research groups about MOOC platforms and as a consideration to choose which one suitable platforms to create, manage, and deliver courses.Â Â